Excavating Values and Character through Angkola-Mandailing Proverbs - Arianto arianto (English Language Teaching Prima Journal (ELT), 2020)
ABSTRACTIt has been undeniable that language variety makes Indonesia world-widely recognized as a unity indiversity country. Language itself is projected to build harmony among other through socialinteraction. In Indonesia, such interactions are commonly beautified with the existences of culturalbased proverbs. As an ethnic group, Angkola-Mandailing (AM) society has been known with itsuniqueness in conducting the proverbs in any traditional event, both joyful celebration (siriaon) andcondolences one (siluluton). Even, in any casual interaction among the citizen. AM proverbs arehighly considered as philosophical and culturally valuable. This research is pointed to describe thefunctions of proverbs and excavating values and character within AM proverbs. Descriptivequalitative was conducted to analyze the data. Further, ethnographic content analysis was alsoemployed to interpret the substances of data analysis. The findings show that AM proverbs arefunctioned to address advice, to admonish, and to satirize. Moreover, the findings also display thatbrotherhood, togetherness, patience, hard-work, sincerity, and respect other people are values andcharacters could be drawn within. To be concluded, the findings are worthwhile to be internalized atpresent.Keywords: Angkola-Mandailing, proverbs, social functions, interpretations